Deflecting my burden, hindering redistribution: How elites influence tax legislation in Latin America - Juan A. Bogliaccini; Juan Pablo Luna (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper proposes to understand a singular but salient factor that enables the wealthy to deflect their tax burden downwards: elites' political leverage to shape legislation via their capacity to influence political actors and policy outcomes. The analysis sheds light on alternative mechanisms used by economic elites over time and space. Our analysis of the political economy of taxing upper-income groups in Chile and Uruguay reveals the importance of continuous political agency on the part of organized elite interest groups. Our results show how even centre-left parties competing on a redistributive programmatic platform confront and concede to the interests of wealthy elites, especially when sustained interaction between political leaders and economic elites becomes routinized in the long run.
Keywords: H24; H25; H26; B40; 330; tax policy; Latin America; elites; tax avoidance; redistribution; case study